A semi-automatic approach to implement rapid non-immersive virtual maintenance simulation. Issue 3 (6th August 2018) - Geng, Jie; Peng, Xu; Li, Ying; Lv, Chuan; Wang, Zili; Zhou, Dong
Abstract : Purpose: Current virtual simulation platforms provide various tools to generate non-immersive simulation processes purposefully in different domains. The generated simulation processes are adopted for analysis, presentation, demonstration and verification. In the virtual maintenance domain, this intuitive and visual method has benefitted product maintainability design and improvement. Generating an ideal and reasonable non-immersive virtual maintenance simulation is always time-consuming because of the complicated human operations and logical relationships involved. This study aims to propose a semiautomatic approach to increase efficiency in non-immersive virtual maintenance simulation implementation. Design/methodology/approach: The methodology analyzes the general catalogs of common maintenance tasks and explores the corresponding secondary development approaches of simulation tools that can achieve motion simulation in virtual environments, by focusing on the diversity, complexity and uncertainty in non-immersive virtual simulation process generation. Afterward, a single virtual human motion can be generated by controlling the parameters and indices of the simulation tools. Subsequently, all of the generated single motions are connected logically to simulate the entire maintenance process. Findings: Instead of selecting various tools, such as that in a traditional method, the proposed methodology analyzes and integrates the necessary basic parameters considering the characteristics of virtual maintenance simulation for a target maintenance activity. Originality/value: The user can control the predefined parameters to generate the simulation combining several other simple operations in virtual environments. Consequently, the methodology decreases simulation tool selection and logic consideration and increases efficiency to a certain extent in non-immersive virtual maintenance simulation generation.